Perilaku Kuat Tekan Beton Normal Terhadap Penambahan Serat Botol Plastik Jenis PET - Noviyanthy Handayani; Amelia Faradila; Imam Juari; Dian Larasati (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
PET (Polyethylene Terephthalate) plastic bottle waste is a material that takes a long time to decompose and will accumulate in the world for a long time. Therefore we need the utilization of the plastic waste. One way to reuse PET plastic bottle waste is to use it as an additive to the concrete mixture. The purpose of this study is to determine how much increase in the compressive strength of concrete to the addition of shredded PET plastic waste at 28 days of concrete. The variations in the addition of 0%, 0,2%, 0,4%, 0,6%, 0,8%, and 1% to the volume of concrete cylinders with 3 samples of concrete variations each. The results showed that the concrete with the addition of PET fibers by 0.2% experienced an increase in the compressive strength value of 1.31% from the compressive strength of normal concrete which was originally 22.251 MPa to 22.650 MPa. While the variation in the percentage of PET 0.4%, 0.6%, 0.8% and 1% decreased the compressive strength of the concrete. In PET fiber concrete 0.6% and 1.0%, although there is a decrease in the average compressive strength of the concrete, the value obtained exceeds the compressive strength value of the concrete plan, which is 20 MPa.